Bag-mask ventilation by low- or untrained rescuers during adult and pediatric resuscitation: a randomized cross-over manikin study - Borremans, Gautier; Geerts, Anke; Coppens, Marc; Christiaens-Leysen, Erik; Herbelet, Sandrine; Van de Voorde, Patrick (Frontiers in Disaster and Emergency Medicine, 2023)
Aim: Bag-mask ventilation (BMV) is often applied during advanced cardiopulmonary resuscitation (CPR). Lay rescuers usually apply mouth-to-mouth ventilation, which is contraindicated in case of potential disease transmission (COVID pandemic). This study evaluates the influence of rescuers' prior This is a provisional file, not the final typeset article BMV training in applying correct BMV during adult and infant CPR. Methods: Medical students (n=112) were enrolled in a randomized cross-over manikin study: 60 first years (53,6%) (untrained, without any prior knowledge of CPR) and 52 fourth years (46,6%) (low trained, with three consecutive years of basic CPR training), excluding BLS certificate holders or lifeguards. Students' duos (2 students from the same year working together), received a 15 minute just-in-time onsite training in full CPR-cycle using BMV and were tested during 5 cycles of 2-person CPR following the ERC guidelines with inclusion of BMV. Tidal volumes of 300-600 ml (adults) and 20-60 ml (infants) were considered as correct ventilations. Results: From the initial 56 duos , 17 (30,3%) were excluded after applying incorrect numbers of ventilation or uninterpretable values. In adult CPR, comparing low-to untrained rescuers in correctly administrating ventilations using BMV after a 15 just-in-time onsite training revealed no statistically significant difference (first years: 63,0% (n=136 out of 216 ventilations); fourth years: 59,5% (n=119 out of 200 ventilations); proportional difference -3.5% [-12.8; 5.9]). In infant CPR, a significant difference was observed in effective ventilations (first years: 55,5% (n=120 out of 216 ventilations); fourth years: 72,3% (n=133 out of 184 ventilations); proportional difference 16.8 [7.25; 26.21]). Conclusion: 2-person BMV is a complex skill both in adults and children, requiring sufficient and regular training. Lay rescuers receiving a 15 minutes just-in-time onsite BMV training could perform decent BMV in an adult CPR setting. BMV during infant CPR requires more extensive prior training and should not be entrusted to lay rescuers, even after a 15 minutes just-intime onsite training.